Unveiling the effect of interacting forecasted abiotic factors on growth and aflatoxin B1 production kinetics by Aspergillus flavus. Issue 2 (February 2021) - Garcia-Cela, Esther; Verheecke-Vaessen, Carol; Gutierrez-Pozo, Maria; Kiaitsi, Elisavet; Gasperini, Alessandra M.; Magan, Naresh; Medina, Angel
Abstract: The aim was to decipher the temporal impact of key interacting climate change (CC) abiotic factors of temperature (30 vs 37 °C), water activity (aw ; 0.985 vs 0.930) and CO2 exposure (400 vs 1000 ppm) on (a) growth of Aspergillus flavus and effects on (b) gene expression of a structural ( aflD ) and key regulatory gene ( aflR ) involved in aflatoxin B1 (AFB1 ) biosynthesis and (c) AFB1 production on a yeast extract sucrose medium over a period of 10 days. A. flavus grew and produced AFB1 very early with toxin detected after only 48 h. Both growth and toxin production were significantly impacted by the interacting abiotic factors. The relative expression of the aflD gene was significantly influenced by temperature; aflR gene expression was mainly modulated by time. However, no clear relationship was observed for both genes with AFB1 production over the experimental time frame. The optimum temperature for AFB1 production was 30 °C. Maximum AFB1 production occurred between days 4–8. Exposure to higher CO2 conditions simulating forecasted CC conditions resulted in the amount of AFB1 produced in elevated temperature (37 °C) being higher than with the optimum temperature (30 °C) showing a potential for increased risk for human/animal health due to higher accumulation of this toxin.